Randomized comparison of health-related quality of life in women with ectopic pregnancy or pregnancy of unknown location treated with systemic methotrexate or expectant management. (September 2015) - van Mello, Norah M.; Mol, Femke; Hajenius, Petra J.; Ankum, Willem M.; Mol, Ben Willem; van der Veen, Fulco; van Wely, Madelon
Abstract: Objective: To study the impact on health-related quality of life (HRQoL) of treatment with systemic methotrexate (MTX) or expectant management in women with ectopic pregnancy or pregnancy of unknown location (PUL) with low and plateauing serum hCG concentrations. Study design: HRQoL was assessed alongside a randomized clinical trial (RCT) with the use of standard self-administered psychometric measure questionnaires. Patients and setting: All women who participated in the multicenter RCT comparing treatment with systemic MTX to expectant management in women with ectopic pregnancy or persisting PUL were eligible for the HRQoL measurements. Main outcome measure: HRQoL measures of three standardized questionnaires (SF-36, RSCL, HADS). Results: Data were available for 64 of 73 women (78%) randomized in the RCT. We found no difference in HRQoL between the two treatment groups. The need for additional treatment, i.e. additional MTX injections or surgical intervention, had no impact on HRQoL. Conclusion: Women treated with MTX or expectant management for an ectopic pregnancy or persisting PUL have comparable quality of life.